Alteration of cortical but not spinal inhibitory circuits in idiopathic scoliosis - Boček, Václav; Krbec, Martin; Vaško, Peter; Brabec, Karel; Pavlíková, Markéta; Štětkářová, Ivana (The journal of spinal cord medicine, 2022)
Background: The pathogenesis of adolescent idiopathic scoliosis (AIS), including the role of brain and spinal inhibitory circuits, is still poorly elucidated. The aim of this study was to identify which central inhibitory mechanisms are involved in the pathogenesis of AIS.Design: A prospective neurophysiological study, using a battery of neurophysiological tests, such as cutaneous (CuSP) and cortical (CoSP) silent periods, motor evoked potentials (MEP) and paired-pulse transcranial magnetic stimulation (ppTMS).Settings: Neurophysiological laboratory.Participants: Sixteen patients with AIS (14 females, median age 14.4) and healthy controls.Outcome measures: MEPs were obtained after transcranial magnetic stimulation (TMS) and recorded from the abductor pollicis muscle (APB). ppTMS was obtained at interval ratios (ISI) of 1, 2, 3, 6, 10, 15 and 20 ms. The cortical silent period (CoSP) was recorded from the APB. The cutaneous silent period (CuSP) was measured after painful stimuli delivered to the thumb while the subjects maintained voluntary contraction of the intrinsic hand muscles. The data were analyzed and compared with those from healthy subjects.Results: The CoSP duration was significantly prolonged in AIS patients. A significantly higher amplitude of ppTMS for ISI was found in all AIS patients, without remarkable left-right side differences. No significant difference in MEP latency or amplitude nor in the CuSP duration was obtained.Conclusion: Our observation demonstrates evidence of central nervous system involvement in adolescent idiopathic scoliosis (AIS). Lower intracortical inhibition, higher motor cortex excitability, and preserved spinal inhibitory circuits are the main findings of this study. A possible explanation of these changes could be attributed to impaired sensorimotor integration predominantly at the cortical level.
Keywords: kosterní svaly; elektrická stimulace; Electric Stimulation; Female; Cutaneous silent period; skolióza; Inhibitory circuit; ženské pohlaví; Adolescent; lidé; transkraniální magnetická stimulace; Motor Cortex; Cortical silent period; poranění míchy; Muscle, Skeletal; motorické evokované potenciály; Electromyography; Spinal Cord Injuries; Evoked Potentials, Motor; prospektivní studie; Prospective Studies; motorické korové centrum; Scoliosis; Adolescent idiopathic scoliosis; Transcranial Magnetic Stimulation; Paired-pulse transcranial magnetic stimulation; mladiství; elektromyografie; Humans